Adaptation of hydrological and anthropogenic risks in peri-urban region : case study of flooding in Pathum Thani Province, Thailand - Dechatorn Wongpaisanlak; Vilas Nitivattananon; Kim, Sohee Minsun; Sarawut Ninsawat; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
Northern Bangkok peri-urban area, especially in Pathum Thani province has faced hydrological and anthropogenic risks, especially flooding. Under high rate of urbanization and population growth, exposure and vulnerability to flood risks increase rapidly. Adaptive capacity to risks is the important aspect which all relevant organization related to flooding problem as well as private sectors and households have to concern. Therefore, this research aims to enhance the adaptive capacity to hydrological risks in peri-urban context of northern Bangkok Metropolitan Region by understanding hydrological risks under climate change, assessing vulnerability to hydrological hazards among urbanization, and providing recommendations for adaptation measures. Pathum Thni province was the representative of the region which is the case study of the research. Climate change and urbanization related hydrological risk is the scope of the research. To grab the whole view of the studied system, DPSIR was a proper framework used in this research. It used to analyze the whole situation of the province. Interview of authorities was done for understand the current situation in depth. Questionnaire survey of 500 people in 2 focused Study Area which categorized by dominant land use were done to assess vulnerability (sensitivity and adaptive capacity) of the system. Focused group meeting was taken place to find out key issues and key adaptations in the future by relevant stakeholders. PT A and OTA are the main method for summarized and analyzed the information. F rom the study, it is obvious that sensitivity of drainage system is the key issues of flooding problems in focused area. More over the problem of W & WW clogging in the pipe of the system also decreased the capacity of the drainage system. While the problem that households along the river did not have the effective strategies to deal with flooding came from lack of knowledge providing to the communities. And increasing of the severity of hazard also came from lack of river dredging. Current adaptive capacity in municipalities of study areas are still lack of long term adaptation capacity in both planned and autonomous measures. Lack of integrated dimension and level of governance was the key factor that caused the operation and management cannot practice effectively. In the other hand, lack of knowledge and awareness raising, and lack of community CSR activities related with flooding are the key issues among households.
A thesis in partial fulfillment of the requirements for the degree of Master of science in Urban Environmental Management
Thesis (M. Sc.) - Asian Institute of Technology, 2018
Keywords: Floods -- Risk assessment -- Thailand -- Pathumthani; Urbanization -- Thailand -- Pathumthani -- Case studies; Climatic changes -- Risk assessment -- Thailand -- Pathumthani